Evaluasi Penggunaan Antibiotik Definitif pada Pasien dengan Infeksi Bakteri Resisten Carbapenem di RSUP Dr. Sardjito, Yogyakarta - Firdhani Satia Primasari; Ika Puspita Sari; Titik Nuryastuti (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2025)
Currently, many countries have reported infections caused by carbapenem-resistant bacteria, and Indonesia is no exception. This condition makes the scope of therapeutic options becomes quite limited. This study aims to evaluate the definitive antibiotics used in patients with carbapenem-resistant bacterial infections along with the calculation of the predictive value of pharmacokinetic parameters which are then linked to the patient's clinical outcome. This research is a retrospective descriptive-analytic study. The subjects of this study were all inpatients with carbapenem-resistant bacterial infections in the period January-March 2020. Antibiotic suitability evaluation was analyzed descriptively, the estimated values ​​of pharmacokinetic parameters were calculated using the pharmacokinetic calculation formula, and the correlation between the estimated pharmacokinetic values ​​and clinical outcomes of the patients was analyzed statistically using Fisher test. The results of the evaluation of definitive antibiotic administration in patients with carbapenem-resistant bacterial infections found that 11 antibiotics met the suitability of the type, dose, frequency, and duration of the 27 antibiotics analyzed. The predicted value of the pharmacokinetic parameters of the 11 definitive antibiotics in the form of minimal levels in the blood at steady state compared to the MIC value showed that 1 (9.1%) antibiotic had a Cssmin value ≥ MIC and 10 (90.9%) other antibiotics had a Cssmin value < MIC. There is no relationship between the predictive value of the pharmacokinetic parameters of definitive antibiotics that meet regimen suitability and clinical outcomes in patients with carbapenem-resistant bacterial infections. In general, although the dosage regimen of definitive antibiotics meet the suitability criteria, drug concentration in blood can be inadequate to eradicate the bacteria due to many factors and can influence the clinical outcomes.